Extratos de macrófitas aquáticas no cultivo de Scenedesmus acuminatus (Lagerheim) Chodat como subsídio à produção de biodisel - Krettle, Raissa Hirle (2015)
The objective of this work was to test the influence of six alternative culture media (one of NPK, two containing Pistia stratiotes and Eichhornia crassipes extracts enriched with NPK, and three with different dilutions of pure extract of E. crassipes (Eic 40, Eic 85, Eic 130) compared to the commercial culture medium ASM-1 in the development of the microalga Scenedesmus acuminatus. Growth rate (K), density, cell volume, biovolume and nutritional quality of culture media were evaluated. The tested media had enough concentration of nutrients for the growth of microalgae. The growth rate of ASM1 (0.439) were similar (p> 0.05) to NPK, NPK + Pis and Eic + NPK. Eic 85 and Eic 130 had the lowest values (0.201; 0.150, respectively) and similar to each other. The volumes of the treatments did not differ to ASM1 (135.427 µm3 ), only Eic + NPK and Eic 130 had lower values (86.780 and 100.401 µm3, respectively). the highest biovolume and cell density were found in Eic + NPK (1.273 mm3 .L-1 and 1047 x 104 cél.mL-1 ). It was concluded that the treatments had very similar nutritional ability to ASM1 and may replace it in the cultivation of S. acuminatus. In particular Eic + NPK with the highest density and biovolume. The treatments with pure extract, despite having lower results, still allowed the development of algae and at zero cost.